Increasing the light extraction and longevity of TMDC monolayers using liquid formed micro-lenses. (7th December 2016) - Woodhead, C S; Roberts, J; Noori, Y J; Cao, Y; Bernardo-Gavito, R; Tovee, P; Kozikov, A; Novoselov, K; Young, R J
Abstract: The recent discovery of semiconducting two-dimensional materials is predicted to lead to the introduction of a series of revolutionary optoelectronic components that are just a few atoms thick. Key remaining challenges for producing practical devices from these materials lie in improving the coupling of light into and out of single atomic layers, and in making these layers robust to the influence of their surrounding environment. We present a solution to tackle both of these problems simultaneously, by deterministically placing an epoxy based micro-lens directly onto the materials' surface. We show that this approach enhances the photoluminescence of tungsten diselenide (WSe2 ) monolayers by up to 300%, and nearly doubles the imaging resolution of the system. Furthermore, this solution fully encapsulates the monolayer, preventing it from physical damage and degradation in air. The optical solution we have developed could become a key enabling technology for the mass production of ultra-thin optical devices, such as quantum light emitting diodes.